Legal Protection for Children Subjected to Forced Labor by Their Parents - Fauzi Anshari Sibarani (International Journal of Sociology and Law, 2026)
Forced labor of children by parents remains a serious issue in the protection of children's rights in Indonesia, especially when such practices are justified on the basis of family economic needs. This study aims to analyze the legal provisions protecting children by forced labor by parents and to examine the obstacles to law enforcement. The research method used is normative legal research by a literature review approach, through an examination of relevant laws, legal principles, and legal doctrines. The findings of the research intricate that, legal positive indonesia there are a good constitutional and juridical legal basis in context is 1945 Constitution of the Republic Indonesia, Child Protection Law, Manpower Law and Convention on The Rights of Children which that make forced child labor as an economic exploitation categorization is prohibited. But the success of legal protection continues to run up against both legal and sociological challenges, including the murky borderlines of forced labour within the family, the challenge of proving psychological coercion and poverty-nurtured cultural attitudes towards child labour. Therefore a comprehensive approach, including law enforcement and social policies based on the best child interest is necessary.